Retrosynthetic Analysis of Centratherolide A - Lee, Nathan S (Technium BioChemMed, 2025)
Centratherolide A is small and permeable, yet it can cause selective irreversible reactions to proteins, including topoisomerase-3β(TOP3B), the only dual RNA and DNA topoisomerase found in humans. Centratherolide A is mainly cytotoxic because of its α-methylene-γ-lactone ring, a potent Michael Acceptor present in their family of Furanoheliangolides and sesquiterpene lactones. Through the common atom analysis, oxidation level analysis, Michael Addition, and common carbon relationships, Centratherolide A was able to be broken down into 7 parts. Trisecting the main chain seems more plausible than bisecting. Further understanding of different R groups and variations propose a possibility of cytotoxicity against other diseases and cancers.